LOCALIZATION THE POSITION OF ROLLING STOCK WITHIN THE MODEL OF RAILWAY NETWORK BY USING AGENT-BASED SIMULATION (Perner's Contacts, 2013)
This article deals with a design of agent-based simulation model using ABAsim architecture and its subsequent utilization in simulation of rolling stock localization within railway network model. The main attention is focused on description of simulation model and all agents involved. The behavior of individual agents is described by means of discrete event language, Coloured Petri Nets.
Keywords: Railway infrastructure models; train positioning; railway traffic simulation; Agent-base simulation